Decoupling Photocurrent Loss Mechanisms in Photovoltaic Cells Using Complementary Measurements of Exciton Diffusion - Curtin, Ian J.; Holmes, Russell J. (Advanced energy materials, 2018)
Significant work has been directed at measuring the exciton diffusion length (LD) in organic semiconductors due to its significance in determining the performance of photovoltaic cells. Several techniques have been developed to measure LD, often probing photoluminescence or charge carrier generation. Interestingly, in this study it is shown that when different techniques are compared, both the diffusive behavior of the exciton and active carrier recombination loss pathways can be decoupled. Here, a planar heterojunction device based on the donor–acceptor pairing of boron subphthalocyanine chloride‐C60 is examined using photoluminescence quenching, photovoltage‐, and photocurrent‐based LD measurement techniques. Photovoltage yields the device relevant LD of both active materials as a function of forward bias subject to geminate recombination losses. These values are used to accurately predict the photocurrent as a function of voltage, suggesting geminate recombination is the dominant mechanism responsible for photocurrent loss. By combining these measurements with photocurrent and photoluminescence quenching, the intrinsic LD, as well as the voltage‐dependent charge transfer state dissociation and charge collection efficiencies are quantitatively determined. The results of this work provide a method to decouple all relevant loss pathways during photoconversion, and establish the factors that can limit the performance of excitonic photovoltaic cells. The exciton diffusion length (LD) determines in part the performance of organic photovoltaic cells. When photoluminescence quenching, photocurrent‐, and photovoltage‐based LD measurements are combined, the LD of both active materials is elucidated and quantitative measures of all relevant photocurrent loss mechanisms are determined as a function of voltage. This provides deeper understanding of loss processes which limit device performance.